L-DOPA increases slow-wave sleep duration and selectively modulates memory persistence in older adults - Isotalus, Hanna K.; Carr, Will J.; Blackman, Jonathan; Averill, George G.; Radtke, Oliver; Selwood, James; Williams, Rachel; Ford, Elizabeth; McCullagh, Liz; McErlane, James; O’Donnell, Cian; Durant, Claire; et al. (Frontiers in Behavioral Neuroscience, 2023)
Millions of people world-wide take medications that increase dopamine activity in the brain for Parkinson's disease. Yet, we do not understand the effect of dopamine on sleep and memory. Our preliminary data in Parkinson’s disease suggests that the timing of dopamine relative to sleep affects the impact of dopamine on long-term memory. Dopamine projections between the midbrain and the hippocampus may support sleep-dependent memory processes after learning, particularly during slow wave sleep. Here we test the hypothesis that dopamine improves memory through modulating NREM sleep. We tested how dopamine affects nocturnal sleep in a double-blind randomised placebo-controlled cross-over trial of healthy older adults (65 to 79 years; n = 35). First, participants learnt a word-list, after which long-acting L-DOPA was administered. Before a full night of sleep, a proportion of those words were re-exposed to strengthen memory. L-DOPA was therefore active during sleep and practice-recognition test, but not during initial learning. A single dose of L-DOPA increased total slow-wave sleep duration compared to placebo by approximately 11%, increasing spindle amplitudes around slow oscillation peaks and around 1-4Hz non-REM spectral power. Behaviourally, L-DOPA worsened memory of words presented only once, relative to re-exposed words. The coupling of spindles to slow oscillation peaks correlated with these differential effects on weaker and stronger memories. To investigate whether this was truly an impact of L-DOPA on consolidation, a second experiment targeting dopamine only to initial encoding or retrieval showed no behavioural effects. These results demonstrate that L-DOPA augments non-REM sleep in elderly, tuning coordinated network activity and impacting selection of information for long-term storage. Pharmaceutical modification of slow-wave sleep and long-term memory may have clinical implications.